Creativity as a predictor of intelligence among undergraduate students - Naderi, Habibollah; Abdullah, Rohani (Marsland Press, 2010)
This research examines the extent to which the level of creativity and different components of creativity: Something about myself, Environmental sensitivity, Initiative, Intellectuality, Self-strength, Individuality and Artistry among undergraduate students predict intelligence. Respondents in the research comprises of 153 from six Malaysian universities. Multiple regression analysis reveals that a total variance in intelligences accounted for by the creativity factors is 13.5% (multiple R2 = 0.135, F (7, 145) =3.222, p = .003). This implies that creativity is important when considering the factors that influence the intelligence of students.